Proceedings of 13th Asian Congress of Pharmaceutical Sciences : progress of pharmacy through technology transfer and adaptation ([Place of publication not identifed] : [publisher not identified], 1990)
The theme of the 13th Asian Congress of Pharmaceutical Sciences was "Progress of Pharmacy Through Technology Transfer and Adaptation". It was held from November 28 to December 1, 1990 at the Philippine International Convention Center, Manila, Philippines with a total of 1,515 participants from different countries. The Organizing Committee was formed as early as January 1989. This was composed of selected active members of the Philippine Pharmaceutical Association. A massive campaign for the active participation of pharmacists was made through the assistance and cooperation of the different provincial and city chapter presidents for the local delegates and presidents of the different FAPA Ordinary and Associate members.
1990 Ishidate FAPA awardees -- FAPA bureau members -- FAPA ordinary and associate members -- FAPA section representative -- General program of 1990 FAPA manila congress -- The 1990 FAPA manila organizing committee -- Opening ceremony program -- Plenary lectures -- Section meetings -- The minutes of bureau meeting -- The minutes of the directorate -- The minutes of the open directorate -- The minutes of the closing session -- Progress of pharmacy -- List of 1990 FAPA manila congress participants.
Sciences :, Proceedings
Keywords: FAPA AWARDEES